2017
DOI: 10.1038/s41598-017-03096-y
|View full text |Cite
|
Sign up to set email alerts
|

Retinol-binding protein-4 expression marks the short-term mortality of critically ill patients with underlying liver disease: Lipid, but not glucose, matters

Abstract: The implications of retinol-binding protein-4 (RBP4) expression in critically ill patients with underlying liver diseases remain unclear. A prospective cohort study involving 200 liver intensive care unit (ICU) patients was conducted, with 274 blood donors as controls. Patient outcomes were assessed using Cox and Kaplan-Meier analyses. Of the 200 ICU patients (mean age: 56.0 yrs), 79.5% were male, 72.5% were cirrhotic, 62% were septic, 29.5% were diabetic, and 29% expired in the ICU (median admission: 7.5 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(56 reference statements)
2
3
0
Order By: Relevance
“… 28 A low concentration of RBP at baseline was found associated with a bad outcome in liver ICU patients, which could predict short-term mortality of the patients, but not long-term mortality. 29 Consistent with these findings, we also present here that RBP level is specifically reduced in the non-survived pneumonia population of the study, indicating that low RBP was the main risk factor for in-hospital mortality in critical pneumonia patients. The predictive performance of the baseline RBP was much better than the severity scoring systems other than CURB-65, which demonstrates it as a better predictor in severe comorbidities.…”
Section: Discussionsupporting
confidence: 90%
“… 28 A low concentration of RBP at baseline was found associated with a bad outcome in liver ICU patients, which could predict short-term mortality of the patients, but not long-term mortality. 29 Consistent with these findings, we also present here that RBP level is specifically reduced in the non-survived pneumonia population of the study, indicating that low RBP was the main risk factor for in-hospital mortality in critical pneumonia patients. The predictive performance of the baseline RBP was much better than the severity scoring systems other than CURB-65, which demonstrates it as a better predictor in severe comorbidities.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were found in the study of patients with ischaemic stroke, showing that elevated serum levels of RBP4 were associated with the severity and poor prognosis of acute ischaemic stroke . However, another two studies of patients admitted in intensive care unit found that low serum RBP4 levels were related to increased mortality in patients with acute exacerbations of chronic obstructive pulmonary disease and underlying liver disease, respectively. The decreased RBP4 levels might attribute to the malnutritional status in these critically ill patients, because circulating RBP4 concentration depends on vitamin A status .…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, Chen et al demonstrated that baseline RBP levels predicted short-term mortality in critically ill patients with underlying liver disease. Interestingly, in this analysis, those patients that survived ICU treatment displayed significantly increased RBP4 levels after ICU discharge [70], highlighting the potential of this biomarker in predicting survival in patients treated on a medical ICU.…”
Section: Selected Adipokines With a Potential Role In Critical Illmentioning
confidence: 99%